Existence of Solution for a Conformable Fractional Cauchy Problem with Nonlocal Condition - Khalid Hilal; Ahmed Kajouni; Najat Chefnaj (International Journal of Differential Equations)
In this work, we prove the existence and uniqueness of mild solution of the fractional conformable Cauchy problem with nonlocal condition. We obtained these results by applying the fixed point theorems precisely to the fixed point theorem of Krasnoselskii and Banach’s fixed point theorem. At the end, we provide application.